Adsorption of chromium and cadmium from wastewater of textile industry by using eggshell - Che Mat, Mohamad Faiz (2016)
Based on Cinzia and Toetti 2009, the textiles industry is one of the industry that contribute to the water pollution. This is because the wastewater of the textiles contains a few heavy metals at high concentration but in this experiment just focusing to the chromium and cadmium. The process treated wastewater from textiles industry is adsorption by using the eggshell. The waste of eggshell is the higher in the Malaysia due to the consumption of eggshell is higher at Malaysia. This research is focusing on the determination of the concentration of chromium and cadmium in the waste water from textile, compare the effectiveness of natural eggshell and calcined eggshell by determine the adsorption rate and determine the isotherm that match the adsorption process. The waste water will be obtained from the Textile Course of Art and Design UiTM Shah Alam, Selangor. The eggshell will be obtained from the restaurants around this area. The eggshell will be washed, dry and crushed by crusher. For the process to make the natural eggshell absorbent it has finished. To make activated carbon, the eggshell will be placed in the furnace at 800°C for 2 hours. The waste water from the textile industry will be undergo the adsorption process using this two adsorbent and it will be tested the concentration of chromium and cadmium using AAS. The result from the experiment show that the wastewater contains higher concentration of chromium and cadmium and it must be treated first before can be released to the stream. The results also show that the activated carbon eggshell has higher efficiency of adsorption compared to the eggshell. Activated carbon eggshell can adsorb the concentration of chromium and cadmium twice better than eggshell. From the value of R² obtain, the Langmuir isotherm is the best to describe this adsorption process because it has the higher value of R². So, the conclusion that can be made that the wastewater of the textile industry should be treated carefully before it discharged to avoid adverse effect to the human and environment.